2022
DOI: 10.1021/acs.energyfuels.2c01484
|View full text |Cite
|
Sign up to set email alerts
|

Role of Organic Matter, Mineral, and Rock Fabric in the Full-Scale Pore and Fracture Network Development in the Mixed Lacustrine Source Rock System

Abstract: The mixed deposition constitutes the external clastic, intrabasinal, and pyroclastic components in both marine and lacustrine environments. The finegrained mixed lacustrine source rocks are rich in organic matter and present good unconventional energy resources. However, the mixed lacustrine source rock systems have extremely low permeabilities and need hydraulic fracturing to stimulate oil from the complex nanoscale matrix. The role of rock fabric, organic matter, and mineral compositions in full-scale pore s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 85 publications
(141 reference statements)
0
6
0
Order By: Relevance
“…We adopted the pore size classification proposed by Yang et al [58] specifically for lacustrine shale, as the pore sizes observed in the Dongyuemiao shale varied significantly. The classification includes micropores (1-10 nm), transitional pores (10-100 nm), mesopores (100-1000 nm), and macropores (more than 1000 nm).…”
Section: Controlling Factors For Physical Propertiesmentioning
confidence: 99%
“…We adopted the pore size classification proposed by Yang et al [58] specifically for lacustrine shale, as the pore sizes observed in the Dongyuemiao shale varied significantly. The classification includes micropores (1-10 nm), transitional pores (10-100 nm), mesopores (100-1000 nm), and macropores (more than 1000 nm).…”
Section: Controlling Factors For Physical Propertiesmentioning
confidence: 99%
“…Moreover, it can be further divided into the III oil bed, clay interlayer bed, II oil bed, I oil bed, and gypsolyte bed from bottom to top. The II oil bed, with a thickness of ∼100 m, is one of the predominant exploration systems for shale oil in the basin. , …”
Section: Geological Settingmentioning
confidence: 99%
“…The II oil bed, with a thickness of ∼100 m, is one of the predominant exploration systems for shale oil in the basin. 25,51…”
Section: Geological Settingmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have revealed that the molecular structure of shale oil generated in its early stages is similar to that of the source rock [12]. The resemblance leads to a strong adsorption affinity between them [13,14], for which shale oil typically adsorbs on the surfaces of microfractures in organic and inorganic pores as oil film [15]. As the generation for hydrocarbon increases, the amount of shale oil may exceed the maximum capacity of Energies 2023, 16, 7253 2 of 14 current sites and migrate into larger adjacent pores and microcracks [16].…”
Section: Introductionmentioning
confidence: 99%